Trade and the global recession - Jonathan Eaton; Sam Kortum; Brent Neiman; John Romalis (National Bank of Belgium, 2010)
The ratio of global trade to GDP declined by nearly 30 percent during the global recession of 2008-2009. This large drop in international trade has generated significant attention and concern. Did the decline simply reflect the severity of the recession for traded goods industries? Or alternatively, did international trade shrink due to factors unique to cross border transactions? This paper merges an input-output framework with a gravity trade model and solves numerically several general equilibrium counterfactual scenarios which quantify the relative importance for the decline in trade of the changing composition of global GDP and changes in trade frictions. Our results suggest that the relative decline in demand for manufactures was the most important driver of the decline in manufacturing trade. Changes in demand for durable manufactures alone accounted for 65 percent of the cross-country variation in changes in manufacturing trade/GDP. The decline in total manufacturing demand (durables and non-durables) accounted for more than 80 percent of the global decline in trade/GDP. Trade frictions increased and played an important role in reducing trade in some countries, notably China and Japan, but decreased or remained relatively flat in others. Globally, the impact of these changes in trade frictions largely cancel each other out.
Keywords: 330; Internationale Wirtschaft; Nationaleinkommen; Gesamtwirtschaftliche Nachfrage; Wirtschaftskrise; Industrie; Gravitationsmodell; Welt